2004
DOI: 10.1007/s00259-004-1719-2
|View full text |Cite
|
Sign up to set email alerts
|

Are dual-phase 18F-FDG PET scans necessary in nasopharyngeal carcinoma to assess the primary tumour and loco-regional nodes?

Abstract: 18F-FDG PET is superior to MRI in identifying lower neck nodal metastasis of NPC. Additional 3-h 18F-FDG PET contributes no further information in the detection of primary tumours or loco-regional metastatic nodes in untreated NPC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 31 publications
0
17
0
4
Order By: Relevance
“…Although some studies have shown that a comparison of FDG uptake in the early phase and that in the delayed phase is useful for distinguishing malignancy from inflammation [18,[21][22][23][24][25][26], from results of our study, a one-phase scan might be sufficient to predict cause-specific survival and local control rates in patients who receive CRT for postoperative locoregional recurrent esophageal cancer. Furthermore, we showed that SUV max in FDG-PET before CRT tended to be correlated with cause-specific survival but not with local control rate.…”
Section: Discussionmentioning
confidence: 87%
“…Although some studies have shown that a comparison of FDG uptake in the early phase and that in the delayed phase is useful for distinguishing malignancy from inflammation [18,[21][22][23][24][25][26], from results of our study, a one-phase scan might be sufficient to predict cause-specific survival and local control rates in patients who receive CRT for postoperative locoregional recurrent esophageal cancer. Furthermore, we showed that SUV max in FDG-PET before CRT tended to be correlated with cause-specific survival but not with local control rate.…”
Section: Discussionmentioning
confidence: 87%
“…These reports have generally been favorable showing improvement in detection or contrast for brain [2], breast [3], lung [4], pancreas [5][6][7], gallbladder [8], hepatocellular [9], cervical [10,11], intra-abdominal [12], intra-thoracic [13], soft-tissue [14], and other tumors [15,16]. For nasopharyngeal carcinoma, high sensitivity did not improve with delayed imaging [17]. Most of these studies demonstrate improvement in contrast or tumor detection; however, in some cases, the RI did not provide incremental improvement, and the change in SUV was in many cases close to the reported reproducibility limit of SUV measurements [18,19].…”
Section: Discussionmentioning
confidence: 93%
“…72 In evaluating the locoregional status of nasopharyngeal carcinoma, the results of a prospective study, including 84 patients, indicated that FDG-PET is superior to MRI in identifying lower neck nodal metastasis, but 3-hour scans did not give further information in detecting both primary tumors or locoregional metastatic nodes with respect to 40-minute images. 73 Nevertheless, it is worth noting that in this study, diazepam 5 mg per os, was routinely given before FDG injection, and this fact might decrease the hexokinase/glucose-6-phosphatase ratio and so render the DP technique ineffective under these circumstances. 74 In fact, diazepam can reduce phosphorylation of glucose by inhibiting hexokinase activity, and its effect after orally administration commences approximately 30 minutes after ingestion and lasts many hours; therefore, it will likely minimally affect the early images (within the first hour), whereas it will significantly influence the FDG uptake on delayed images.…”
Section: Other Tumorsmentioning
confidence: 87%